New information on the ancestry of modern South American chicken - CGIAR Research Program on Livestock (2020)
Journal article on European/Asian contribution to the genetic diversity of mainland South American chicken. Better understanding of the origins of chicken genome diversity may guide ex-situ conservation priorities, and contribute to discovery of genetic variants for economic and ecologically important traits and admixture analysis of an individual animals breed composition.